Impact of RFID Technology on Logistic Process Efficiency in Retail Supply Chains - Svetlana Nikoličić; Milorad Kilibarda; Predrag Atanasković; Ljubica Duđak; Andrea Ivanišević (Promet - Traffic&Transportation, 2015)
The challenges that logistics faces in the retail industry must be investigated in the context of the specific retail sector as well as the degree of development of the retail market. The research focus in this paper is on logistic processes in supermarket supply. The aim is to deepen the understanding of logistic processes and then to investigate the possibilities of their enhancement by applying radio frequency identification (RFID) as a higher level of information technology for product identification in retail supply chains. The research was conducted in one of the top ten trade companies in the emerging Serbian market. Simulation modelling was performed for one supply chain category, followed by quantification of time and cost performance of the current logistic processes (AS-IS model). Then, in accordance with the capabilities of RFID system, improvements are proposed and integrated into a new simulation model (TO-BE model). The obtained results can be utilised as part of a broader research when deciding on the implementation of modern information technologies in supply chains.